Investigation of cutting parameters in milling of din 1.2379 and sleipner materials - GİRİT, OĞUZ (My University, 2022)
In today???s machining conditions, the goal is to produce the most suitable quality with the lowest cost. In order to minimize the problems of mouth spillage, especial-ly those used in cutting molds, we have studied Sleipner material as an alternative material and examined the machinability parameters between DIN 1.2379 mate-rial used in the application. In this study, with the aid of a force gauge, the forces generated on the material during machining, the surface roughness values after machining with the help of surface roughness device and the temperature values of the materials during machining were measured with the temperature gauge. A total of twelve experiments were carried out for each material at three different chip depths at constant cutting speed and four different progressions for each chip depth. These experiments have been understood from the results obtained from the data that Sleipner material has shown a more stable structure and better results than DIN 1.2379. Thus, the negative manufacturing conditions that may occur during mold production and during mold operation are minimized. In this case, it is necessary to take into consideration the number of the parks produced in the mold and the frequency of mold usage in the material selection of the cutting steel of the cutting molds.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; TERMODİNAMİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); THERMODYNAMICS; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Physical Sciences; Sleipner material; DIN 1; 2379; cutting parameter; frequency; cutting steel; cutting mold